2011
DOI: 10.1017/s1751731111000796
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation with selenium-enriched yeast or sodium selenite on selenium tissue distribution and meat quality in commercial-line turkeys

Abstract: The objective of this study was to determine the concentration of total selenium (Se) and proportions of total Se comprised as selenomethionine (SeMet) and selenocysteine (SeCys) in the tissues of female turkeys offered diets containing graded additions of selenized-enriched yeast (SY), or sodium selenite (SS). Oxidative stability and tissue glutathione peroxidase (GSH-Px) activity of breast and thigh muscle were assessed at 0 and 10 days post mortem. A total of 216 female turkey poults were enrolled in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
42
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 29 publications
14
42
2
Order By: Relevance
“…Glandular visceral tissues tend to have greater total Se concentrations than muscle tissue and cardiac muscle has a greater Se content than skeletal tissue or gizzard tissue. These data agree with those reported in laying hens (Petrovič et al, 2006;Pan et al, 2007), broilers (Wang and Xu, 2008), turkeys (Juniper et al, 2011) and are also similar to those reported in lambs (Juniper et al, 2008a) and beef cattle (Juniper et al, 2008b). …”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Glandular visceral tissues tend to have greater total Se concentrations than muscle tissue and cardiac muscle has a greater Se content than skeletal tissue or gizzard tissue. These data agree with those reported in laying hens (Petrovič et al, 2006;Pan et al, 2007), broilers (Wang and Xu, 2008), turkeys (Juniper et al, 2011) and are also similar to those reported in lambs (Juniper et al, 2008a) and beef cattle (Juniper et al, 2008b). …”
Section: Discussionsupporting
confidence: 91%
“…The lack of effect of any significant response over time in whole blood and plasma Se concentrations of Con birds would be expected and is consistent with the findings of other authors (Echevarria et al, 1988;Pan et al, 2007;Yoon et al, 2007;Juniper et al, 2011). However, the Se values recorded in the T 0 group and Con birds were higher than those recorded in commercial lines of poultry in other studies that had received diets, which had not been augmented with supplementary Se (Petrovič et al, 2006;Yoon et al, 2007 andJuniper et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations